2015
DOI: 10.1080/17588928.2015.1044427
|View full text |Cite
|
Sign up to set email alerts
|

Attentional control and the self: The Self-Attention Network (SAN)

Abstract: Although there is strong evidence that human decision-making is frequently self-biased, it remains unclear whether self-biases mediate attention. Here we review evidence on the relations between self-bias effects in decision-making and attention. We ask: Does self-related information capture attention? Do self-biases modulate pre-attentive processes or do they depend on attentional resources being available? We review work on (1) own-name effects, (2) own-face effects, and (3) self-biases in associative matchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
336
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(379 citation statements)
references
References 75 publications
36
336
3
4
Order By: Relevance
“…Without the goal of retrieving a specific memory, autobiographically significant concepts are free to trigger a cascade of related memories. An intriguing question for future research is whether these self-relevant stimuli automatically bias attention away from the external environment (Humphreys & Sui, 2016) and towards episodic simulation, even at times when it is deemed inappropriate (e.g., when attempting to focus on another task). Although there is considerable evidence that episodic simulation serves adaptive functions, there is also evidence that it is subject to various pitfalls (Schacter, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Without the goal of retrieving a specific memory, autobiographically significant concepts are free to trigger a cascade of related memories. An intriguing question for future research is whether these self-relevant stimuli automatically bias attention away from the external environment (Humphreys & Sui, 2016) and towards episodic simulation, even at times when it is deemed inappropriate (e.g., when attempting to focus on another task). Although there is considerable evidence that episodic simulation serves adaptive functions, there is also evidence that it is subject to various pitfalls (Schacter, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the behavioural and heamodynamic evidence, ERP studies in visual attention have demonstrated that distracters in spatial attention tasks elicit brain responses indicative of top-down suppression (distracter positivity, Pd), rather than attentional selection (the N2pc component), of those distracters in space (Hickey et al, 2009;Sawaki and Luck, 2010;Schubö, 2010, 2011;McDonald et al 2012;Gaspar and McDonald, 2014). These findings have jointly suggested that in real-world environments stimuli not matching the current goals of the observer have little ability to attract the observer's attention (with the 4 exception, maybe, of stimuli whose task-relevance is 'hardwired' in the brain; e.g., Koster et al, 2004;Humphreys and Sui, 2015;Matusz et al, 2015a;Munneke et al, 2015).…”
Section: Introductionmentioning
confidence: 91%
“…ERPs showed that this was the case-there was differential medial frontal activation for high and low rewards when gambling for self, but not when gambling for another. Providing further depth to Humphreys and Sui's (2016) SAN proposal, this suggested that the self-processing biases linked to mPFC activation may not be limited to attention. Rather, items associated with self also elicit affective responses linked to reward circuitry that may also impact on subsequent processing.…”
Section: The Current Issuementioning
confidence: 99%
“…Based on evidence including neural responses to the shape-association task, Humphreys and Sui (2016) have proposed that self-relevant stimuli activate a neural "self-attention network" (SAN), with perception of self-relevant stimuli triggering responses in areas such as ventromedial prefrontal cortex (vmPFC) and the left posterior superior temporal sulcus (LpSTS). Humphreys and Sui suggest that the vmPFC's robust link with self-referential processing (Kelley et al, 2002;Macrae et al, 2004;Northoff et al, 2006) is a result of its role in cascading information that stimuli are self-relevant to the LpSTS attentional system, which then elicits attentional and perceptual biases.…”
Section: Background: the Self In Cognitionmentioning
confidence: 99%